Perlindungan Hukum Terhadap Tanah Hak Milik Masyarakat Pasca Bencana Alam Erupsi Gunung Sinabung - Fitriani Fitriani; Masitah Pohan; Ida Nadirah (Iuris Studia: Jurnal Kajian Hukum, 2021)
Indonesia is located in a natural disaster prone location where various types of natural disasters, including earthquakes and tsunamis, volcanoes, floods, landslides, droughts, forest and land fires, and other natural disasters still occur very frequently. Post natural disaster events also have a systemic impact on land issues, especially for areas that are most severely affected by natural disasters, where one of the impacts is the loss of land boundaries caused by changes in land surface due to natural disasters, mainly caused by the earthquake and tsunami.The problems raised in this study, namely how the rule of law against community land rights after the Mt. Sinabung eruption natural disaster, the position and status of community property rights after the Mt. Sinabung eruption natural disasters and legal protection of community land ownership after the eruption. Mount Sinabung.To find answers to these problems, this research uses descriptive analytical normative legal research, where this normative legal research uses secondary data as primary data and also uses primary data as complementary data using data collection techniques carried out by means of literature study, as well as Qualitative data analysis.The rule of law for community property rights after the natural disaster of the Mt. Sinabung eruption is broadly regulated in Article 27 of Law Number 5 of 1960 Concerning Basic Agrarian Regulations which states that one of the causes of the abolition of ownership rights is because the land was destroyed, however, this provision does not automatically mean that the community's community-owned land can be abolished. There are a number of activities that must be carried out until the community's community-owned land is removed. The position and status of community property rights after the natural disaster of the Mt. Sinabung eruption, which basically remains the property of victims of natural disasters and victims of disasters do not lose their property rights before the disaster belongs to disaster victims. The state cannot directly control the ex-disaster land even though the land owner has died. Land ownership should still be returned to the community, especially for areas that are still inhabited by indigenous peoples. Legal protection of community land rights after the occurrence of natural disaster of the Mt. Sinabung eruption is through legal protection of individual ownership holders and protection through land consolidation and relocation activities